2009
DOI: 10.1213/ane.0b013e3181907ebe
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Provides Anxiolysis, Enhances Analgesia, Decreases Intraocular Pressure, and Promotes Better Operating Conditions During Cataract Surgery Under Topical Anesthesia

Abstract: We concluded that oral melatonin premedication for patients undergoing cataract surgery under topical anesthesia provided anxiolytic effects, enhanced analgesia, and decreased IOP resulting in good operating conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
120
6
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 24 publications
8
120
6
1
Order By: Relevance
“…Several studies have used VAS to analyze pre-surgery anxiety. Findings have shown that average VAS values range between 40 and 50 for a cataract operation under topical anesthesia (8,15) and between 50 and 60 prior to other surgical procedures (9,16), whereas moderate or severe anxiety was found in 65.5% of women prior to a cesarean section (17). These values are higher than those found in our study.…”
Section: Main Endoscopic Diagnosis Principal (N %)contrasting
confidence: 77%
See 1 more Smart Citation
“…Several studies have used VAS to analyze pre-surgery anxiety. Findings have shown that average VAS values range between 40 and 50 for a cataract operation under topical anesthesia (8,15) and between 50 and 60 prior to other surgical procedures (9,16), whereas moderate or severe anxiety was found in 65.5% of women prior to a cesarean section (17). These values are higher than those found in our study.…”
Section: Main Endoscopic Diagnosis Principal (N %)contrasting
confidence: 77%
“…Some are also used in the case of colonoscopy (4,5,8,9). Therefore, if the state of anxiety is clinically significant it is possible to resort to such methods to improve the situation All the above circumstances justify the need to carry out the study, with the objective of analyzing the frequency and degree of outpatient colonoscopy anxiety in our hospital, as well as determining the factors which cause this effect, and its influence on the tolerance of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Because melatonin reduces IOP in experimental models, it would be of interest to see whether this effect is also feasible in humans. In this sense, some ophthalmologists have started to use melatonin to reduce IOP in patients undergoing cataract surgery, indicating the relevance of this molecule as regulator of IOP (Ismail and Mowafi, 2009), suggesting its possible use as a treatment of ocular hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways for drugs to reach the ocular system, for instance, melatonin orally administered at a concentration of 10 mg to patients before performing cataract surgery have shown to lower intraocular pressure, consequently, they had better operating condition [20]. Melatonin was also investigated for the treatment of uveitis in hamsters, experiments were done by injecting 5 mg of melatonin before the induction of uveitis, and results suggested that melatonin prevents the clinical and biochemical consequences of this disorder [21].…”
Section: Short Commentarymentioning
confidence: 99%